Intravitreal bevacizumab alone or combined with triamcinolone acetonide as the primary treatment for diabetic macular edema - Marey HM (Dove Medical Press, 2011)
Hatem M Marey, Amin F EllakwaOphthalmology Department, Minoufiya University, EgyptPurpose: To compare the efficacy of intravitreal injection of bevacizumab alone or combined with intravitreal triamcinolone as the primary treatment for cases with diabetic macular edema (DME).Methods: Ninety eyes were enrolled in one of the three study arms; where intravitreal triamcinolone acetonide (IVT) was used in group I, IVT/intravitreal bevacizumab (IVT/IVB) in group II, and IVB in group III. The visual acuity (VA) and central macular thickness (CMT) were used as the outcome measures, where the results of each group were calculated and compared with the results of the other.Results: There was significant improvement in the VA in the three study groups at weeks 6 and 12; with regards to the intraocular pressure (IOP), there was significant difference at week 6 in the IVT and IVT/IVB groups, and at week 12 in IVT/IVB group, and nonsignificant difference at week 6 in the IVB group and at week 12 in IVT and IVB groups.Conclusion: From this study, we conclude that IVB is an effective drug for treatment of DME, and has a long lasting effect when compared with IVT and when compared with combined IVT/IVB; adding IVT does not affect the outcome measures except for elevating the IOP in treated patients in the early post-injection period.Keywords: visual acuity, central macular thickness, intraocular pressure, IVT, IVB